KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DALAM PERMAINAN TRADISIONAL AWI ALU - Agatha, Sance Cristina; Boleng, Lukas Maria; Bali, Engelbetus Nggalu (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2021)
The aim is to know and describe the gross motor skills of children through the traditional Awi Alu game and to find out the supporting and inhibiting factors in the traditional Awi Alu game. The research method used is qualitative with data collection techniques used are observation, interviews and documentation. The data and research results that have been collected are then analyzed descriptively. The results of the research on the gross motor skills of children aged 5-6 years in playing the traditional games of Awi Alu at Paud Lili Maumere can be seen that the gross motor skills of children in jumping include; (1) strength aspect (2) aspect (3) aspect (4) speed aspect (5) coordination aspect. Supporting factors in the traditional game of Awi Alu, among others; (1) the students' motivation to play is quite high. (2) supporting facilities and environment for the process of implementing traditional games. While the factors that hinder the implementation of game activities include: (1) the concentration of students who fluctuate easily. (2) insufficient time to play the game. (3) the development of times and technology regarding the types of games.